2012 A-level H2 Mathematics (9740) Paper 1 Question 3 Suggested Solutions

All solutions here are SUGGESTED. Mr. Teng will hold no liability for any errors. Comments are entirely personal opinions.

(i)
u_2 = u_{1+1} = \frac{3u_1 - 1}{6} = \frac{5}{6}

u_3 = \frac{3u_2 -1}{6} = \frac{1}{4}

(ii)
As n \rightarrow \infty, u_n \rightarrow l, u_{n+1} \rightarrow l

\Rightarrow l = \frac{3l-1}{6}

6l = 3l - 1

l = -\frac{1}{3}

(iii)
Let P(n) be the statement “u_n = \frac{14}{3} (0.5)^{n} - \frac{1}{3}” for n \in {\mathbb{Z}}^{+}

When n = 1, \mathrm{LHS} = u_1 = 2,~ \mathrm{RHS} = \frac{14}{3}(0.5) - \frac{1}{3} = 2 = \mathrm{LHS}.

Thus, P(1) is true.

Assume P(k) is true for some k \in \mathbb{Z}^{+}, i.e.

u_k = \frac{14}{3} (0.5)^{k} - \frac{1}{3}

To prove P(k+1) is true, i.e.

u_{k+1} = \frac{14}{3} (0.5)^{k+1} - \frac{1}{3}

\mathrm{LHS}

= u_{k+1}

= \frac{3u_{k}-1}{6}

= \frac{1}{6} [14 (0.5)^{k} - 1-1]

= \frac{1}{6} [14 (0.5)^{k} - 1-1]

= \frac{14}{6} 2 (0.5)^{k+1} - \frac{1}{3}

= \frac{14}{3} (0.5)^{k+1} - \frac{1}{3}

= \mathrm{RHS}

Since P(1) is true, by Mathematical Induction, P(k) is true \Rightarrow P(k+1) is true, P(n) is true for all n \in \mathbb{Z}^{+}

KS Comments:

This question is quite straight forward. Some students did not realise to use the given recurrence relation to solve the MI.

Leave a Comment

4 × 4 =

Contact Us

CONTACT US We would love to hear from you. Contact us, or simply hit our personal page for more contact information

Not readable? Change text. captcha txt

Start typing and press Enter to search